Influence of temperature on sintering behavior and properties of TiC-Fe-Co-Ni-Cr-Mo cermets. Issue 17 (1st December 2017) - Zhuang, Qiming; Lin, Nan; He, Yuehui; Kang, Xiyue
Abstract: Sintering behavior of TiC-Fe-Co-Ni-Cr-Mo cermets with excellent mechanical properties and corrosion resistance was researched systematically by measurements of hardness, transverse rupture strength, scanning electron microscopy, X-ray diffraction and Tafel extrapolation. Results showed that with increase in sintering temperature, the hardness of sintered cermets increased constantly, while the transverse rupture strength initially increased and then decreased. Transverse rupture strength of cermets sintered at 1290 °C reached peak value of 2358.1 MPa. Moreover, cermets sintered at 1370 °C with transverse rupture strength of 1514 MPa and hardness of 67.6 HRC showed the best abrasive resistance and Icorr values of 1.611×e −7 .